2000
DOI: 10.1037/0022-3514.79.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Perceived superiority in close relationships: Why it exists and persists.

Abstract: Two studies used a thought-listing technique to examine perceived superiority, or the inclination to regard one's own relationship as better than (and not as bad as) others' relationships. Consistent with the claim that this is a motivated phenomenon--and motivated in part by strong commitment--Study 1 revealed that (a) tendencies toward perceived superiority and (b) the commitment-superiority link are both strongest given psychologically threatening instructions and weakest given accuracy instructions (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
196
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 211 publications
(203 citation statements)
references
References 55 publications
(134 reference statements)
6
196
1
Order By: Relevance
“…For example, one influential program of research by Griffin (1996a, 1996b) has extended earlier work by Taylor and Brown (1988) on positive illusions from the realm of individuals to that of couples, arguing that long-term relational satisfaction is most likely when the partners hold idealized views of each other. Rusbult et al (2000) similarly found greatest relational endurance and satisfaction among partners who perceived themselves as superior to other couples. Although such correlational findings preclude causal conclusions, they parallel results from other domains suggesting that an inflated, even delusional sense of optimism and positivity is not only adaptive, but can also prove self-fulfilling (see Reed, Kemeny, Taylor, Wang, & Visscher, 1994).…”
Section: Close Relationshipsmentioning
confidence: 73%
“…For example, one influential program of research by Griffin (1996a, 1996b) has extended earlier work by Taylor and Brown (1988) on positive illusions from the realm of individuals to that of couples, arguing that long-term relational satisfaction is most likely when the partners hold idealized views of each other. Rusbult et al (2000) similarly found greatest relational endurance and satisfaction among partners who perceived themselves as superior to other couples. Although such correlational findings preclude causal conclusions, they parallel results from other domains suggesting that an inflated, even delusional sense of optimism and positivity is not only adaptive, but can also prove self-fulfilling (see Reed, Kemeny, Taylor, Wang, & Visscher, 1994).…”
Section: Close Relationshipsmentioning
confidence: 73%
“…Moreover, because dependence constitutes reliance on a partner for fulfilling important needs, increasing dependence yields persistence in interactions and longevity in relationships (Bui et al 1996, Drigotas & Rusbult 1992. To reduce the vulnerabilities inherent in such reliance, dependence also yields patterns of cognition and affect that quell feelings of insecurity and promote congenial interaction (e.g., positive illusion, downward comparison) , Rusbult et al 2000.…”
Section: Dimensions Of Situation Structurementioning
confidence: 99%
“…For example, commitment emerges as a consequence of dependence on a specific partner and thus is strengthened as a result of high satisfaction, poor alternatives, and high investments (Rusbult et al 2001). Commitment colors emotional reactions to challenging interaction situations (feeling affection rather than anger when a partner is neglectful) and gives rise to habits of thought that support the decision to persist (use of plural pronouns, positive illusion, derogation of alternatives) (Agnew et al 1998, Johnson & Rusbult 1989, Rusbult et al 2000. In turn, benevolent thoughts and feelings promote prosocial transformation, especially in situations of moderate to high correspondence.…”
mentioning
confidence: 99%
“…positive illusions about the partner; Murray, Holmes, & Griffin, 1996; derogation of alternatives; Johnson & Rusbult, 1989;Simpson, Gangestad, & Lerma, 1990; perceived superiority of the relationship; Buunk & Van der Eijnden, 1997;Rusbult, Van Lange, Wildschut, Yovetich, & Verette, 2000).…”
mentioning
confidence: 99%